Mato Grosso do Sul on the Growth Route: an investigation into the potentialities driven by the Bioceanic Route - Constantino, Michel (2023)
This article aimed to investigate the relationship between the potential of economic growth in Mato Grosso do Sul with the implementation of the Bioceânica Route. Using studies carried out and published since 2015, the analysis structures and defines the main potentialities in the macroeconomic and sectoral scope for Mato Grosso do Sul. The results defined five points of analysis: i. Accelerated economic growth; ii. Expansion of international trade; iii. Investment in infrastructure; iv. Development of new production chains and v. Strengthening the strategic position of the state. A radar analysis and the probability distribution of impact on each point listed after the definitive implementation of the Route was prepared, which could lead the state of Mato Grosso do Sul to the Route of Growth.